Juxtaposition of Bub1 and Cdc20 on phosphorylated Mad1 during catalytic mitotic checkpoint complex assembly - Fischer, Elyse S.; Yu, Conny W. H.; Hevler, Johannes F.; McLaughlin, Stephen H.; Maslen, Sarah L.; Heck, Albert J. R.; Freund, Stefan M. V.; Barford, David (Nature communications, 2022)
In response to improper kinetochore-microtubule attachments in mitosis, the spindle assembly checkpoint (SAC) assembles the mitotic checkpoint complex (MCC) to inhibit the anaphase-promoting complex/cyclosome, thereby delaying entry into anaphase. The MCC comprises Mad2:Cdc20:BubR1:Bub3. Its assembly is catalysed by unattached kinetochores on a Mad1:Mad2 platform. Mad1-bound closed-Mad2 (C-Mad2) recruits open-Mad2 (O-Mad2) through self-dimerization. This interaction, combined with Mps1 kinase-mediated phosphorylation of Bub1 and Mad1, accelerates MCC assembly, in a process that requires O-Mad2 to C-Mad2 conversion and concomitant binding of Cdc20. How Mad1 phosphorylation catalyses MCC assembly is poorly understood. Here, we characterized Mps1 phosphorylation of Mad1 and obtained structural insights into a phosphorylation-specific Mad1:Cdc20 interaction. This interaction, together with the Mps1-phosphorylation dependent association of Bub1 and Mad1, generates a tripartite assembly of Bub1 and Cdc20 onto the C-terminal domain of Mad1 (Mad1 CTD ). We additionally identify flexibility of Mad1:Mad2 that suggests how the Cdc20:Mad1 CTD interaction brings the Mad2-interacting motif (MIM) of Cdc20 near O-Mad2. Thus, Mps1-dependent formation of the MCC-assembly scaffold functions to position and orient Cdc20 MIM near O-Mad2, thereby catalysing formation of C-Mad2:Cdc20. Formation of the mitotic checkpoint complex (MCC) is catalysed by a phosphorylation-dependent scaffold. This work provides structural details of how a tripartite Mad1:Bub1:Cdc20 complex presents Cdc20 to Mad2, triggering open-to-closed conversion of Mad2 to assemble the MCC.